Effects of Gd3+ and Ce3+ on seed germination and growth of tomato and quinoa plants - Francesca Giuliano; Dario Nicola Tangredi; Francesco Guarino; Stefano Castiglione; Angela Cicatelli (Plant Biosystems, 2026)
Several studies reported that rare earth elements (REEs) can exert both beneficial and harmful effects on plants, including improved seed germination, plant growth, and crop yield. However, these findings remain controversial and highly variable, likely due to differences in the specific REEs investigated, their concentrations, and the plant species studied. In our study we assessed the effects of increasing concentrations of gadolinium (Gd) and cerium (Ce), together with sodium citrate (used as chelating agent), on two important plant species: tomato ( Solanum lycopersicum ) and quinoa ( Chenopodium quinoa ). The aim was to establish the effects on seed germination and seedling growth, also detecting the presence of hormesis through the application of a statistical model. Seeds were placed in Petri dishes on filter paper soaked with the corresponding solution (from 10 μM to 150 μM; deionized water used as control). After germination, shoot and root length were measured and several indexes related to germination and initial seedling growth were calculated. The results highlighted species-specific and concentration-dependent responses. In quinoa roots, Ce induced a subtle biphasic dose–response trend characterized by a growth stimulation at low concentrations (10 μM) and inhibition at higher levels. Instead, tomato shoot length increased under both REEs, while high Gd doses negatively impacted on root growth. Low concentrations of REEs could be a successful approach to stimulate plant development, particularly in initial growth stages. Nevertheless, their mechanisms and the suitable dosage remain unclear, determining the need for further studies, especially to assess the long-term effects on ecosystems.

Constructed wetlands as a sustainable solution for domestic wastewater treatment in Egypt - Carmen Tammone; Ranya A. Amer; Tarek H. Taha; Reham M. Elkout; Francesco Guarino; Angela Cicatelli; Gianmaria Oliva; Stefano Castiglione (Journal of Environmental Chemical Engineering, 2026)

Optimizing CO2 capture: Effects of chemical functionalization on woodchip biochar adsorption performance - Antonio Faggiano; Angela Cicatelli; Francesco Guarino; Stefano Castiglione; Antonio Proto; Antonino Fiorentino; Oriana Motta (Journal of Environmental Management, 2025)

Efficient phytoremediation of first-flush storm water using an innovative constructed wetland: a pilot-scale study towards sustainable water reuse - Carmen Tammone; Dario Nicola Tangredi; Angela Cicatelli; Francesca Giuliano; Ivano Spiniello; Francesco Guarino; Stefano Castiglione (Plant Biosystems, 2025)

Antibiotic resistance in urban soils: Dynamics and mitigation strategies - Annamaria Gentile; Luca Di Stasio; Gianmaria Oliva; Giovanni Vigliotta; Angela Cicatelli; Francesco Guarino; Werther Guidi Nissim; Massimo Labra; Stefano Castiglione (Environmental Research, 2024)

Epigenetic changes induced by chronic and acute chromium stress treatments in Arabidopsis thaliana identified by the MSAP-Seq - Francesco Guarino; Angela Cicatelli; Werther Guidi Nissim; Ilaria Colzi; Cristina Gonnelli; Marcos Fernando Basso; Chiara Vergata; Felice Contaldi; Federico Martinelli; Stefano Castiglione (Chemosphere, 2024)

Reduction of antimicrobial resistance: Advancements in nature-based wastewater treatment - Annamaria Gentile; Paolo Piccolo; Patrizia Iannece; Angela Cicatelli; Stefano Castiglione; Francesco Guarino (Journal of Hazardous Materials, 2024)

Landfill leachate treatment by a combination of a multiple plant hybrid constructed wetland system with a solar photoFenton process in a raceway pond reactor - Ivano Spiniello; Marco De Carluccio; Stefano Castiglione; Enzhe Amineva; Natalia Kostryukova; Angela Cicatelli; Luigi Rizzo; Francesco Guarino (Journal of Environmental Management, 2023)

Transgenerational effects of chromium stress at the phenotypic and molecular level in Arabidopsis thaliana - Ilaria Colzi; Cristina Gonnelli; Chiara Vergata; Gabriele Golia; Andrea Coppi; Maria Beatrice Castellani; Antonio Giovino; Matteo Buti; Tommaso Sabato; Maurizio Capuana; Alessio Aprile; Luigi De Bellis; et al. (Journal of Hazardous Materials, 2023)

Tall-statured grasses: a useful functional group for invasion science - Susan Canavan; Laura A. Meyerson; Jasmin G. Packer; Petr Pyšek; Noëlie Maurel; Vanessa Lozano; David M. Richardson; Giuseppe Brundu; Kim Canavan; Angela Cicatelli; Jan Čuda; Wayne Dawson; et al. (Biological Invasions, 2019)

In vitro propagation of Leucocroton havanensis Borhidi (Euphorbiaceae): A rare serpentine-endemic species of Cuba - Dubiel Alfonso; Angela Cicatelli; Francesco Guarino; Daymara Rodríguez; Stefano Castiglione (Plant Biosystems, 2018)

Reclamation of Cr-contaminated or Cu-contaminated agricultural soils using sunflower and chelants - Angela Cicatelli; Francesco Guarino; Stefano Castiglione (Environmental Science and Pollution Research, 2017)

Use of Zea mays L. in phytoremediation of trichloroethylene - Emanuele Moccia; Adriano Intiso; Angela Cicatelli; Antonio Proto; Francesco Guarino; Patrizia Iannece; Stefano Castiglione; Federico Rossi (Environmental Science and Pollution Research, 2017)

Global networks for invasion science: benefits, challenges and guidelines - Jasmin G. Packer; Laura A. Meyerson; David M. Richardson; Giuseppe Brundu; Warwick J. Allen; Ganesh P. Bhattarai; Hans Brix; Susan Canavan; Stefano Castiglione; Angela Cicatelli; Jan Čuda; James T. Cronin; et al. (Biological Invasions, 2017)

Erratum to: Genetic and biochemical characterization of rhizobacterial strains and their potential use in combination with chelants for assisted phytoremediation - Angela Cicatelli; Francesco Guarino; Enrico Baldan; Stefano Castiglione (Environmental Science and Pollution Research, 2017)

Genetic and biochemical characterization of rhizobacterial strains and their potential use in combination with chelants for assisted phytoremediation - Angela Cicatelli; Francesco Guarino; Enrico Baldan; Stefano Castiglione (Environmental Science and Pollution Research, 2017)

Epigenetic control of heavy metal stress response in mycorrhizal versus non-mycorrhizal poplar plants - Angela Cicatelli; Valeria Todeschini; Guido Lingua; Stefania Biondi; Patrizia Torrigiani; Stefano Castiglione (Environmental Science and Pollution Research, 2014)